The Experimentation Act and its Practice of Autonomous Vehicles in Taiwan - Chang, Li-Ching (International Journal of Membrane Science and Technology, 2023)
Taiwan has invested considerable sums of human capital and material resources in the practical application of autonomous vehicles for more market opportunity. As on-road testing and technological development for autonomous vehicles continue to develop in different countries, the controversial issues of safety, ethics, liability, and the invasion of privacy continue to emerge. In order to resolve these issues, the government of Taiwan seeks to provide a good environment for AI innovation and applications. This article summarizes and highlights relevant content and key points of Unmanned Vehicles Technology Innovative Experimentation Act, which was legislated in Taiwan in 2018. In addition, with introduction to the progress and achievement after the implementation of the Act, the article also explains the development and prospection of autonomous vehicles in Taiwan.